SEEDGT: Secure and energy efficient data gathering technique for IoT applications based WSNs. (June 2022) - Salim, Ahmed; Osamy, Walid; Aziz, Ahmed; Khedr, Ahmed M.
Abstract: Internet of Things based Wireless Sensor Networks (IoT-WSNs) are widely employed in a variety of applications, including military, health-care, and industrial monitoring. Security parameters are essential to protect the network from various security threats and attacks because these applications handle sensitive information in potentially hostile and unattended environments. This paper aims to achieve the security parameters for IoT applications based WSNs by proposing a secure and energy aware data gathering technique, called SEEDGT, which integrates between trust, public key algorithm, and Compressive Sensing (CS) methods towards achieving security with fair energy load balance in IoT-WSN. The proposed SEEDGT technique has three phases, namely Cluster formation, network operation and reconfiguration phase. During the cluster formation phase, energy-aware and trust based methods are applied for the creation of clusters and cluster head selection. The network operation phase aims to achieve security by using the public key algorithm to encrypt network data during the data gathering process. Moreover, in this phase, CS strategy is employed to reduce the original data size, which leads to a reduction in energy usage. Finally, the changes that could occur during network operations is considered through the reconfiguration phase. The simulation studies illustrate that SEEDGT is effective in achieving better performance than other baseline approaches.